2007
DOI: 10.1002/chin.200706179
|View full text |Cite
|
Sign up to set email alerts
|

12/10‐ and 11/13‐Mixed Helices in α/γ‐ and β/γ‐Hybrid Peptides Containing C‐Linked Carbo‐γ‐amino Acids with Alternating α‐ and β‐Amino Acids.

Abstract: Peptides U 0400 12/10-and 11/13-Mixed Helices in α/γand β/γ-Hybrid Peptides Containing C-Linked Carbo-γ-amino Acids with Alternating αand β-Amino Acids. -(SHARMA*, G. V. M.; JADHAV, V. B.; RAMAKRISHNA, K. V. S.; JAYAPRAKASH, P.; NARSIMULU, K.; SUBASH, V.; KUNWAR, A. C.; J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…16 All the peptides were prepared from corresponding monomers of carbo-ˇ3-and 4 -amino acids (derived from D-xylose) by conventional methods using 1-(3-dimethylaminopropyl)-3-ethylcarbodimide hydrochloride (EDCI) and 1-hydroxy benzotriazole hydrate (HOBt) in dichloromethane.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 All the peptides were prepared from corresponding monomers of carbo-ˇ3-and 4 -amino acids (derived from D-xylose) by conventional methods using 1-(3-dimethylaminopropyl)-3-ethylcarbodimide hydrochloride (EDCI) and 1-hydroxy benzotriazole hydrate (HOBt) in dichloromethane.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Talaty et al reported an interesting mass spectral study on the influence of the presence and position of an alternative amino acid including two nonnatural amino acids viz.ˇ-alanine (X), -aminobutyric acid (X) on the formation of b n C and y n C ions from a series of protonated tetrapeptides with general sequence XAAG, AXAG, and AAXG. 39 In continuation of our studies, here we report on ESI MS/MS of a new series of hybrid peptides comprising the repeats ofˇ3-Caa- 4 -Caa (ˇ, -)/ 4 -Caa-ˇ3-Caa ( ,ˇ-) 16 (Scheme 1).…”
Section: E=1; R=hmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive ion ESI mass spectra of all these peptides (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) + ions (Scheme 2). Fragmentation of these peptides can be explained by using the nomenclature, which was originally proposed for α-peptides by Roepstorff and Fohlman, and later modified by Biemann [18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Oligomers of non-natural peptidic residues [4][5][6], particularly with β-amino acids [7,8] and their hybrids with natural L-amino acids have emerged as versatile structural templates (foldamers) as these exhibit predictable and welldefined secondary structures such as helices, turns, and strands, and offer a variety of possibilities for orienting functional sidechains [9][10][11][12][13]. The oligomers of these amino acids both in cisand trans-conformation have exhibited diverse helical patterns in solution [12][13][14].…”
Section: Introductionmentioning
confidence: 99%